Reference Ranges for Hemoglobin and Hematocrit Levels in Neonates as a Function of Gestational Age (22-42 Weeks) and Postnatal Age (0-29 Days): Mathematical Modeling - Felix Scholkmann; Daniel Ostojic; Helene Isler; Dirk Bassler; Martin Wolf; Tanja Karen (MDPI AG, 2019)
Hematological values of neonates need to be interpreted taking into account the fact that the reference ranges depend on the age of the neonate. We aimed to derive two general mathematical models for reference ranges for hemoglobin concentration (cHb) and hematocrit (Hct) levels in neonates as a function of gestational age (GA) and postnatal age (PNA), since it is known that GA and PNA are independent factors determining cHb and Hct. For this purpose, cHb and Hct values from the data set of Henry and Christensen (2015, Clin. Perinatol., 42, 483-497) from about 100,000 neonates (GA: 22-42 weeks, PNA: 0-28 days) were used and general models with two quadratic functions were derived. To the best of our knowledge, the models we have developed are the first published ones to provide reference ranges for cHb and Hct for neonates incorporating the parallel dependence on GA and PNA.